Tuberculous meningitis: many questions, too few answers. - Thwaites, G; Tran, T (2005)
Tuberculous meningitis (TM) is difficult to diagnose and treat; clinical features are non-specific, conventional bacteriology is widely regarded as insensitive, and assessment of newer diagnostic methods is not complete. Treatment includes four drugs, which were developed more than 30 years ago, and prevents death or disability in less than half of patients. Mycobacterium tuberculosis resistant to these drugs threatens a return to the prechemotherapeutic era in which all patients with TM died. Research findings suggest that adjunctive treatment with corticosteroids improve survival but probably do not prevent severe disability, although how or why is not known. There are many important unanswered questions about the pathophysiology, diagnosis, and treatment of TM. Here we review the available evidence to answer some of these questions, particularly those on the diagnosis and treatment of TM.